2018
DOI: 10.1051/0004-6361/201731292
|View full text |Cite
|
Sign up to set email alerts
|

The optical/NIR afterglow of GRB 111209A: Complex yet not unprecedented

Abstract: Context. Afterglows of Gamma-Ray Bursts (GRBs) are simple in the most basic model, but can show many complex features. The ultra-long duration GRB 111209A, one of the longest GRBs ever detected, also has the best-monitored afterglow in this rare class of GRBs. Aims. We want to address the question whether GRB 111209A was a special event beyond its extreme duration alone, and whether it is a classical GRB or another kind of high-energy transient. The afterglow may yield significant clues. Methods. We present af… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 247 publications
(335 reference statements)
2
50
3
Order By: Relevance
“…A broken power law showed no such excess (e.g., Greiner et al 2015;Kann et al 2016), so this excess is modeldependent. Moreover, a single power law was used by Cano et al (2016), and no such excess was observed, making it inconclusive.…”
Section: Modeling the Light Curves Of Sn 2011klmentioning
confidence: 93%
See 4 more Smart Citations
“…A broken power law showed no such excess (e.g., Greiner et al 2015;Kann et al 2016), so this excess is modeldependent. Moreover, a single power law was used by Cano et al (2016), and no such excess was observed, making it inconclusive.…”
Section: Modeling the Light Curves Of Sn 2011klmentioning
confidence: 93%
“…The G15 LC did not include the NIR contribution and is a pseudobolometric LC. By adding the NIR contribution, Kann et al (2016) obtained a genuine bolometric LC (the K16 LC)…”
Section: Modeling the Light Curves Of Sn 2011klmentioning
confidence: 99%
See 3 more Smart Citations